TUTORIAL SESSION IN COMPARISON TO PROBLEM-BASED LEARNING IN UNDERGRADUATE CANDIDATES OF MEDICAL AND DENTAL COLLEGE - AdminSamia Perwaiz Khan; Muhammad Ali Zubair; Marium Younus Paracha (ziauddin University, 2024)
Background: Tutor has an essential role in conducting tutorial sessions and encouraging effective learning in students. The tutor develops learning objectives, monitors and clarifies the queries of students. Whereas students learn to understand and teach each other by participating and this helps the students better understand the subject and gain deeper knowledge of the various topics of each module in medical curriculum. The advantage of these sessions is to improve students understanding of topic, allowing time for discussion, and making them, self-learners. Problem-based learning (PBL) is a tool in medical education to teach and learn basic and clinical concepts in medicine and become self-learner. Aim of the study was, to evaluate the significance of tutorials as effective learning tool and was compared to problem - based learning for medical and dental undergraduate students, for topic understanding, time required to understand the topic, filling in gaps in knowledge and improvement in examination scores. Methods: Tutorial sessions and PBL were conducted as small group learning in Department of Pharmacology, Jinnah Medical and Dental College, Karachi, Pakistan. In each class of undergraduate MBBS and BDS, students were distributed into 10-12 students groups. Students, from MBBS III year students and BDS II year, participated in this study and filled in questionnaires at the end of tutorial sessions. Comparison of tutorial and PBL sessions were evaluated by a second questionnaire by MBBS undergraduate students. Conclusion: The study participants were undergraduate students of MBBS and BDS. They found the tutorial sessions were effective tool. Although in comparison to tutorial, the students found problem-based learning more significant in understanding concepts of medical curriculum.